2011
DOI: 10.1103/physreva.84.043644
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Monte Carlo calculations for unitary fermions in a harmonic trap

Abstract: We present a new lattice Monte Carlo approach developed for studying large numbers of strongly interacting nonrelativistic fermions and apply it to a dilute gas of unitary fermions confined to a harmonic trap. In place of importance sampling, our approach makes use of high statistics, an improved action, and recently proposed statistical techniques. We show how improvement of the lattice action can remove discretization and finite volume errors systematically. For N = 3 unitary fermions in a box, our errors in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
81
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 55 publications
2
81
1
Order By: Relevance
“…Furthermore, comparing with the results of Ref. [4], it seems clear that one would need much larger lattices in the Galilean-invariant version to make Fig. 6 look like Fig.…”
Section: Appendix A: Evaluation Of S(η)mentioning
confidence: 90%
“…Furthermore, comparing with the results of Ref. [4], it seems clear that one would need much larger lattices in the Galilean-invariant version to make Fig. 6 look like Fig.…”
Section: Appendix A: Evaluation Of S(η)mentioning
confidence: 90%
“…This is due to an "overlap problem" which affects calculations in all areas of physics (see, e.g., Ref. [22]). The Monte Carlo estimates of Ĥ were obtained by averaging over 10 4 de-correlated samples of the auxiliary field, which ensured a statistical uncertainty of order 1%.…”
Section: A Ground-state Energy and Contactmentioning
confidence: 99%
“…[1][2][3][4][5][6][7], that the second cumulant of log C(t), κ 2 , increases roughly linearly with time t.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] have shown that, for their data sets, noisy signals can be tamed by replacing the average correlator by a truncated cumulant sum,…”
mentioning
confidence: 99%
See 1 more Smart Citation